Evaluación del marketing digital y su influencia en el capital de marca en restaurantes de la ciudad de Manta - García Cortez, Omar Alexander (2023)
The research work was carried out with the objective of evaluating digital marketing and its influence on the brand capital in restaurants in the city of Manta for the determination of strategies, its development had a methodology based on the types of research: descriptive, bibliographic , field and exploratory, likewise, methods such as: analytical, correlational, inductive and deductive were used, where a survey was applied to a sample of 100 establishments, their selection was made through a non-probabilistic sampling for convenience. For their part, the results obtained fall on the identification of indicators for the study variables, for digital marketing it was used: e-commerce, level of use of social networks, promotion and consumer-connection; and for brand capital, the following was used: loyalty, awareness, perceived quality and the image of the brand, in addition, the result of the survey, its level of correlation and significance between the variables was 0.544, being a considerable positive correlation and its bilateral significance. very significant, in addition, the causes that limit the actions of marketing were identified, such as the lack of generation of stimuli, difficulty in offering quality, among others, finally, digital marketing strategies were proposed through the use of the 5w + 1h matrix Having said this, in summary of the study, it was identified that digital marketing does significantly affect the brand capital of restaurants and that actions in digital media are positively related to brand awareness.